أثر السياسة النقدية والمالية على تدفقات الاستثمار الأجنبي المباشر في الجزائر دراسة قياسية للفترة (1990-2012 - علاوي, محمد لحسن; بوروشة, كريم (جامعة الوادي University of Eloued, 2015)
ملخص: تهدف هذه الدراسة بشكل أساسي إلى استقصاء أثر السياسة النقدية والمالية المتبعة على تدفقات الاستثمار الأجنبي المباشر الوارد إلى الجزائر خلال الفترة (1996- 2012) وذلك من خلال تطبيق نموذج الانحدار الذاتي المتجه (VAR) على بيانات سنوية، حيث تم اختيار معدل اعادة الخصم، الكتلة النقدية(M2) وسعر الصرف كمتغيرات للسياسة النقدية، النفقات العمومية كمتغير للسياسة المالية إضافة إلى قيمة الاستثمار الأجنبي الواردة إلى الجزائر كمتغير للاستثمار الأجنبي. بينت نتائج الدراسة وجود علاقة سببية في اتجاه واحد بين كل من الانفاق العام، كتلة النقود ومعدل إعادة الخصم من جهة، وتدفقات الاستثمار الأجنبي المباشر الوارد للجزائر من جهة أخرى،كما بينت أيضا وجود قوة تفسيرية للإنفاق العام و الكتلة النقدية في تفسير التغيرات في قيمة الاستثمار الأجنبي، وبشكل عام، أظهرت النتائج وجود تأثير ايجابي ومعنوي للسياسة النقدية والمالية على الاستثمار الأجنبي، وبالتالي يمكن القول أن نتائج هذه الدراسة جاءت منسجمة مع النظرية الاقتصادية. Abstract: This study is mainly aimed to the impact of monetary and fiscal policy on inward FDI to Algeria during the period flows survey (1996- 2012). Through the application of self-regression vector model (VAR) on annual data, was chosen as the re-discount rate, the block Cash (M2) and exchange rate variables for monetary policy, fiscal policy as a variable of public expenditure as well as the value of incoming foreign investment to Algeria as a variable for foreign investment. The results of the study and a causal relationship in one direction between each of the public spending, Money supply and the rate of re-discount on the one hand, and the flows of FDI to Algeria on the other hand. Also showed the presence of explanatory power of public spending and the money supply in the interpretation of changes in the value of the investment foreign, and in general. The results showed a positive and significant effect of monetary and fiscal policy on foreign investment, and thus we can say that the results of this study were consistent with economic theory.
The impact of monetary and fiscal policy on foreign direct investment flows in Algeria "Empirical Study for the period 1990-2012 "
مقال- مجلة رؤى اقتصادية
Keywords: السياسة النقدية، السياسة المالية، الاستثمار الأجنبي، الانحدار الذاتي المتجه، الجزائر; Monetary policy, fiscal policy, foreign investment, self-gradient vector, Algeria.